MILITARY-PEDAGOGICAL ORIENTATION OF MILITARY SPECIALIST TRAINING - Gorodianska, L. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The military-pedagogical process is a complex socio-psychological phenomenon. Its essence lies in purposeful, motivated, substantive organizational and educational activities of all its subjects. This activity is aimed at preparing the military specialists who are able to successfully perform their functional duties both in peacetime and in modern war conditions. The strength of the country's defense capability and combat readiness in modern conditions is ensured by a high level of intellectual potential of the Armed Forces of Ukraine. This potential is being formed as a set of potentials of highly qualified personnel of military specialists. Today the task of reforming military education is not limited only to structural and functional transformations of the educational base and restructuring of the educational process. It is necessary to create an environment (a system of higher military education) for constant spiritual and professional improvement of the individual and motivation to achieve a high level of military professionalism. Access of educational institutions to modern information technologies contributed to the emergence of interactive forms of learning and transformation of the subject of learning from a passive participant and its active involvement in the learning process. Given the development of digital technologies and the difficult state in which Ukraine found itself due to military action and the negative epidemiological situation, it is appropriate to create a system of higher military education using the subject-activity approach and the introduction of forms of distance learning. It is proposed to direct the military-pedagogical training of specialists along six lines. The assessment of the level of conformity of a serviceman's actual professional qualities with the requirements to the occupied military position is important in the professional-psychological selection in the Armed Forces. That is why it is expedient to develop a model of recreation of intellectual potential of servicemen and a methodology for evaluating the general level of intellectual resources of the Armed Forces of Ukraine. In the basis of construction of such model it is offered to put directions of military-pedagogical training of military specialists together with professionally important criteria of evaluation of recreating of moral-psychological qualities of servicemen of the Armed Forces of Ukraine.
Keywords: professional training, training subject, recreating of military specialists' intellectual potential, military-pedagogical orientation, model of recreation of serviceman's intellectual potential